# `lim_(x->0^+) ln(x)/x` Find the limit. Use l’Hospital’s Rule where appropriate. If there is a more elementary method, consider using it. If l’Hospital’s Rule doesn’t apply,...

`lim_(x->0^+) ln(x)/x` Find the limit. Use l’Hospital’s Rule where appropriate. If there is a more elementary method, consider using it. If l’Hospital’s Rule doesn’t apply, explain why.

*print*Print*list*Cite

Expert Answers

sciencesolve | Certified Educator

You need to evaluate the given limit, such that:

`lim_(x->0^+) (ln x)/x = (ln 0^+)/(0^+)`

`lim_(x->0^+) (ln x)/x = (-oo)*1/(0^+)`

`lim_(x->0^+) (ln x)/x = -oo*(+oo) = -oo`

**Hence, evaluating the given limit yields using the rule that the limit of the product is the product of the limits, yields `lim_(x->0^+) (ln x)/x = -oo.` **